Réponses

2012-11-18T12:32:55+01:00

les identités pour la dérivé? f(x)=\frac{u(x)}{v(x)} alors f'(x)=\frac{u'(x)v(x)-v'(x)*u(x)}{v(x)²}

 

et pour la deuxième tu utilises f(x)=u(x)v(x) alors f'(x)=u'(x)v(x)+v'(x)u(x)

 

f(x)=\frac{\sqrt{x}}{x^5}

 

tu prends u(x)=√x et v(x)=x⁵

d'où

f'(x)=\frac{\frac{1}{2\sqrt{x}} - 4x*\sqrt{x}}{x^{10}}

soit:

 

f'(x)=\frac{-8x^2+1}{x^{10}*2\sqrt{x}}

 

 

et la deuxième u(x)= 2√x v(x)=(1+√x)

 

f(x)= 2√x(1+√x)

donc:

f'(x)= \frac{2(1+\sqrt{x})}{2\sqrt{x}} + \frac{2\sqrt{x}}{2\sqrt{x}}

 

donc f'(x)= \frac{4\sqrt{x}+2}{2\sqrt{x}}

 

f'(x)=\frac{2\sqrt{x}+1}{\sqrt{x}}